Aeroservoelastic simulations for horizontal axis wind turbines. (March 2017) - Prasad, CS; Chen, Q-Z; Bruls, O; D'Ambrosio, F; Dimitriadis, G
This paper describes the development of a complete methodology for the aeroservoelastic modelling of horizontal axis wind turbines at the conceptual design stage. The methodology is based on the implementation of unsteady aerodynamic modelling, advanced description of the control system and nonlinear finite element calculations in the Samcef Wind Turbines design package. The aerodynamic modelling is carried out by means of fast techniques, such as the blade element method and the unsteady vortex lattice method, including a free wake model. The complete model also includes a description of a doubly fed induction generator and its control system for variable speed operation. The Samcef Wind Turbines software features a nonlinear finite element solver with multi-body dynamics capability. The full methodology is used to perform complete aeroservoelastic simulations of a realistic 2 MW wind turbine model. The interaction between the three components of the approach is carefully analysed and presented here.